2010
DOI: 10.1182/blood-2010-02-268649
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1/2 and extension study of velaglucerase alfa replacement therapy in adults with type 1 Gaucher disease: 48-month experience

Abstract: Enzyme replacement therapy is the standard of care for symptomatic Gaucher disease. Velaglucerase alfa is a human ␤-glucocerebrosidase produced in a wellcharacterized human cell line. A 9-month phase 1/2 open-label, single-center trial and ongoing extension study were conducted to evaluate safety and efficacy of velaglucerase alfa. Twelve symptomatic adult type 1 Gaucher patients (intact spleens) received velaglucerase alfa (60 U/kg per infusion) during phase 1/2. An extension study was offered to patients com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
93
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 10 publications
5
93
0
7
Order By: Relevance
“…Collectively, these studies demonstrated that velaglucerase alfa was generally well tolerated among both treatment‐naïve and switch patients including children, adults, pregnant patients, and geriatric patients 2, 3, 4, 5, 6. There were few drug‐related serious adverse events (AEs) and the vast majority of AEs were classified by the investigators as infusion related and considered to be mild to moderate and transient in nature.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Collectively, these studies demonstrated that velaglucerase alfa was generally well tolerated among both treatment‐naïve and switch patients including children, adults, pregnant patients, and geriatric patients 2, 3, 4, 5, 6. There were few drug‐related serious adverse events (AEs) and the vast majority of AEs were classified by the investigators as infusion related and considered to be mild to moderate and transient in nature.…”
Section: Introductionmentioning
confidence: 95%
“…One case of anaphylactoid reaction was reported (<1%) 5. Overall, <1% of patients developed anti‐drug antibodies following exposure to velaglucerase alfa and no patients developed IgE antibodies 2, 3, 4, 5, 6.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations